2012
DOI: 10.1007/s10646-011-0837-4
|View full text |Cite
|
Sign up to set email alerts
|

The use of cellular diagnostics for identifying sub-lethal stress in reef corals

Abstract: Coral reefs throughout the world are exhibiting documented declines in coral cover and species diversity, which have been linked to anthropogenic stressors including land-based sources of pollution. Reductions in coastal water and substratum quality are affecting coral survivorship, reproduction and recruitment, and hence, the persistence of coral reefs. One major obstacle in effectively addressing these declines is the lack of tools that can identify cause-and-effect relationships between stressors and specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…We have shown that Hsp70 has the ability to respond to an abiotic stressor (low DO concentration) within two weeks, even in relatively stress-tolerant bivalves [61], prior to detectable effects on growth or survival. Understanding sublethal stress to predict and avoid species loss has broad applications, and has been identified as important to management of communities from recreational fisheries to coral reefs as well as to contaminant monitoring [62][64]. Our data support the idea that protein biomarkers, measured in sentinel species such as oysters, provide a promising approach to identify suitable sites for restoration, particularly to capture negative effects of habitat quality on biota before lethal impacts are incurred.…”
Section: Discussionsupporting
confidence: 62%
“…We have shown that Hsp70 has the ability to respond to an abiotic stressor (low DO concentration) within two weeks, even in relatively stress-tolerant bivalves [61], prior to detectable effects on growth or survival. Understanding sublethal stress to predict and avoid species loss has broad applications, and has been identified as important to management of communities from recreational fisheries to coral reefs as well as to contaminant monitoring [62][64]. Our data support the idea that protein biomarkers, measured in sentinel species such as oysters, provide a promising approach to identify suitable sites for restoration, particularly to capture negative effects of habitat quality on biota before lethal impacts are incurred.…”
Section: Discussionsupporting
confidence: 62%
“…Since the earliest steps of an organism's response to any environmental stress occur at the cellular level (Kultz 2005), a useful diagnostic tool can be represented by the analysis of the expression of cellular stress molecular biomarkers that reflect changes in the cellular structural integrity and in the functional cellular pathways and performance (Downs 2005). Such an approach has been successfully applied in corals subjected to several abiotic stresses (Downs et al , 2009(Downs et al , 2012Brown et al 2002;Downs and Downs 2007;Rougee et al 2006;Fitt et al 2009;Kenkel et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of xenobiotics on the coral animal have been studied in detail, revealing specific genes that respond to heavy metal stress (Morgan et al 2005), oil dispersants, vinblastine (Venn et al 2009), pesticides, and antifouling paints (Downs et al 2012). However, very little is known regarding the influence of xenobiotics on the microbial component of the coral holobiont.…”
Section: Xenobiotic-associated Functional Genesmentioning
confidence: 99%